Estudo da formação de coacervatos com nitrosilos complexos de rutênio - Sampaio, Nayara Syndel Franco Soares (2013)
This work reports the preparation of a new coacervate by mixture of aqueous solution of sodium polyphosphate and nitrosyl ruthenium complexes. The complexes used were: cis-[Ru(bpy)2(L)(NO)]n+, where L = 1-methylimidazole (MeimN), imidazole (ImN) and sulfite (SO32-). The preparation of the coacervates is possible only when ethanol is used. In accord of characterization of the coacervates the electronic absorption spectroscopy (UV-Vis) shows the characteristics bands of complex indicating their presence in the coacervates. Even after the preparation of the coacervates the infrared spectra show the presence of the NO+ group. Therefore, the preparation doesn’t change the form (oxidation state) of the NO ligand attached in the complexes. The nuclear magnetic resonance (NMR) 1H spectra have showed the signals of the hydrogen of the ligands into the coordination sphere of the complexes. Several compositions to coacervates are possible only changing the initial concentration of the complexes into mixture. The aqueous solution of sodium polyphosphate and the coacervates have showed interesting features related to conversion process nitrosyl-nitro. The conversion process nitrosyl-nitro occurs slowly into aqueous solution of the sodium polyphosphate at pH 7,0 but into the coacervates there’s no evidence of conversion process nitrosyl-nitro during 12 months. The shifting of the metal-ligand charge-transfer (MLCT) band from 332nm to 450nm was used to evaluated the conversion process nitrosyl-nitro by electronic absorption spectroscopy (UV-Vis). The release of the nitric oxide in the coacervates was induced by photochemical and chemical reduction. In both situations the release occurred and the complexes showed the properties of the nitric oxide releasing.